2012
DOI: 10.1302/0301-620x.94b10.29184
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with surgical site infection in 30 491 primary total hip replacements

Abstract: We examined patient and surgical factors associated with deep surgical site infection (SSI) following total hip replacement (THR) in a large integrated healthcare system. A retrospective review of a cohort of primary THRs performed between 2001 and 2009 was conducted. Patient characteristics, surgical details, surgeon and hospital volumes, and SSIs were identified using the Kaiser Permanente Total Joint Replacement Registry (TJRR). Proportional-hazard regression models were used to assess risk factors for SSI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 29 publications
9
131
2
2
Order By: Relevance
“…After removal of duplicates and screening, 109 articles were assessed for eligibility. Finally, 12 observational cohort studies [30][31][32][33][34][35][36][37][38][39][40][41] comparing LAF with conventional ventilation in the OR were identified. Most investigators described the ventilation system used in the control group as "conventional (plenum)" or "ordinary" ventilation system, 30,32,36,39,40 while others reported the use of "conventional turbulent ventilation with HEPA-filtered air".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates and screening, 109 articles were assessed for eligibility. Finally, 12 observational cohort studies [30][31][32][33][34][35][36][37][38][39][40][41] comparing LAF with conventional ventilation in the OR were identified. Most investigators described the ventilation system used in the control group as "conventional (plenum)" or "ordinary" ventilation system, 30,32,36,39,40 while others reported the use of "conventional turbulent ventilation with HEPA-filtered air".…”
Section: Resultsmentioning
confidence: 99%
“…Most investigators described the ventilation system used in the control group as "conventional (plenum)" or "ordinary" ventilation system, 30,32,36,39,40 while others reported the use of "conventional turbulent ventilation with HEPA-filtered air". 31,37,38 In four studies, investigating THA 34 and TKA 35,41 performed in the USA between 2000 and 2009 and gastric surgery 33 performed in the Republic of Korea between 2010 and 2011, the authors did not provide additional information about the ventilation system of the ORs without LAF. These studies were included after discussion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound contamination at the time of the procedure is thought to be a cause of early postoperative infections [10,13,17,18]. Recent studies have shown increased wound contamination and infection rates with the use of modern surgical helmet systems compared with conventional gowns, and it has been hypothesized that the positive pressure within a surgical helmet system may potentially underlie the higher rates of wound contamination and infection [7,11,12,18]. The purpose of our study was to determine the amount of particle contamination at the gown-glove interface in several modern surgical helmet systems as well as conventional gowns.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the extent of postsurgical inflammatory reaction correlates with the severity of pain experienced by patients after total joint arthroplasty [15]. Obesity has recently been found to be an independent risk factor for severity of postoperative pain after musculoskeletal surgery and for risk of surgical site infection after THA [21,23]. Although the exact underlying mechanisms remain obscure, some of the consequences and complications of obesity likely are caused by the condition.…”
Section: Introductionmentioning
confidence: 99%